Relationship between serum prealbumin level and prognosis of community-acquired bacterial meningitis in adults: a retrospective cohort study - Shang, Jing; Xue, Lanping; Zhao, Hongping; Cui, Xiaopeng; Shangguan, Lijuan; Wang, Hailong; Li, Xinyi (Frontiers in Neurology, 2024)
Background Low serum prealbumin levels have been identified as a predictor of infectious complication in critically ill patients. However, the association in patients with Community-acquired bacterial meningitis (CABM) remains unclear. The aim of this study is to investigate the relationship of prealbumin and the poor outcome of CABM through a retrospective cohort study. Methods A total of 77 patients of CABM were enrolled. They were divided into good outcome group (GOS: 5) and a bad outcome group (GOS: 1–4). Serum prealbumin and other clinical records were measured within 24 h after admission. Results Among the included patients, 38(65.52%) had a bad outcome (the GOS score between 1 and 4). The mean age of the overall cohort was 45.3 ± 15.9 years, and 58.6% of patients were male. The mean prealbumin level in the bad outcome group was 115.4 ± 49.4 mmol/L, while the mean level in the good outcome group was 199.1 ± 49.3 mmol/L (p < 0.001). Individuals with plasma prealbumin level ≤180 mmol/L had a 3.32-fold higher risk of CABM than those with normal plasma prealbumin level [OR = 4.32 (1.02 18.24), p < 0.05]. Conclusion Reduced plasma prealbumin level is independently associated with the poor outcome of CABM. Plasma prealbumin level might help to identify patients at high risk of bad outcome.